Study on Shorting Mechanism to Promote the Construction of Internal Control System of Listed Companies: Based on Muddy Waters' shorting of Huishan Dairy Perspective - Chen, Xinxin (International Journal of Global Economics and Management, 2024)
In order to explore the promotion effect of shorting mechanism on the internal control of listed companies, this paper takes Muddy Waters' shorting of Huishan Dairy as an entry point to explore the internal control deficiencies faced by Huishan Dairy in the event. The analysis shows that the enterprise has problems such as fragile control environment, imperfect risk assessment system, poor implementation of control activities and lack of internal supervision. In response to these problems, this paper puts forward a series of optimization strategies and recommendations, aiming to provide valuable reference and reference for enterprises in the same industry to strengthen the construction of internal control, and help enterprises to build a more solid management cornerstone.